The South Pole‐Aitken Basin: Constraints on Impact Excavation, Melt, and Ejecta - R. I. Citron; D. E. Smith; S. T. Stewart; L. L. Hood; M. T. Zuber (Geophysical Research Letters)
Abstract The formation and evolution of the South Pole‐Aitken (SPA) basin is critical to relating large impact basin formation and modification to lunar geophysical evolution. Most prior models of the SPA impact were conducted in 2D, making it difficult to compare model output to the 3D crustal structure and ejecta distribution. In order to better constrain the parameters of the SPA impactor and the expected post impact distribution of crust and ejecta, we conducted numerical simulations of the SPA impact in 3D. We tested a wide range of impact parameters and constrained model results with recent geophysical data. We found the crustal structure of the SPA basin is best fit by an oblique impact (30–45°) of a 350–400 km diameter projectile impacting at 12–16 km/s. The impact excavated material from as deep as 80–120 km, and ejecta was deposited in a butterfly pattern with a forbidden region uprange of the impact.